LARANGAN PERKAWINAN ANTARA SEPUPU SEJAJAR DI MASYARAKAT ADAT DAYAK KENINJAL DESA BINA JAYA KECAMATAN TANAH PINOH KABUPATEN MELAWI - NIM. A1011201004, STEPANUS JERRY (Fakultas Hukum Universitas Tanjungpura, 2024)
ABSTARCTPROHIBITION OF MARRIAGES BETWEEN EQUAL COUSINS IN DAYAK KENINJAL INDIGENOUS COMMUNITY OF BINA JAYA VILLAGE TANAH PINOH DISTRICT MELAWI REGENCY Marriage customs are an important event in the lives of the Dayak Keninjal indigenous people. Marriage is a holy and sacred thing to establish a life-long relationship until death do us part, so there are customary prohibitions when carrying out a marriage which can be seen in the family tree. The prohibition on marriage between equal cousins is a marriage that is related by blood, this is considered taboo or malicious because it does not respect the ancestors and hurts the hearts of indigenous people. Marriage customs in Bina Jaya Village, Tanah Pinoh District, Melawi Regency have been passed down from generation to generation. As time went by, the Dayak Keninjal Traditional Marriage experienced a shift in the regulations related to the Prohibition of Married Cousins. One of them is the customary fine, the amount of which has been determined and can be reduced depending on the agreement. Then several objects that are requirements for marriage, such as knives, jugs, cloth, can be replaced with money according to the value of the objects that are conditions for marriage. In this research the author formulates the problem of